1980
DOI: 10.1111/j.1476-5381.1980.tb07891.x
|View full text |Cite
|
Sign up to set email alerts
|

Renin‐angiotensin Mediation of Adrenal Catecholamine Secretion Induced by Hypoglycaemia in the Cat

Abstract: The mechanism involved in catecholamine (CA) release from the cat adrenal gland in response to insulin hypoglycaemia was studied. In intact cats, hypoglycaemia induced an 11 fold increase in adrenomedullary CA secretion. Acute bilateral nephrectomy nearly abolished the increased CA release from the adrenal gland during hypoglycaemia. Infusion of Sar1‐Ileu8‐Angiotensin II (AII), a competitive AII antagonist, suppressed the adrenomedullary response to the insulin‐induced hypoglycaemia. After termination of the a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

1990
1990
2012
2012

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…Thus exogenous angiotensin II stimulates Epi secre-tion in vivo (24), and high concentrations of angiotensin II stimulate Epi release from isolated perfused adrenals (33). Furthermore, nonselective angiotensin II receptor blockade with [Sar,Ile]-angiotensin abolishes adrenomedullary catecholamine release during insulin-induced hypoglycemia (4). We showed that the increase in plasma Epi concentration during insulininduced hypoglycemia is unaltered by selective AT 1receptor blockade in both rats and humans (34,35).…”
mentioning
confidence: 70%
“…Thus exogenous angiotensin II stimulates Epi secre-tion in vivo (24), and high concentrations of angiotensin II stimulate Epi release from isolated perfused adrenals (33). Furthermore, nonselective angiotensin II receptor blockade with [Sar,Ile]-angiotensin abolishes adrenomedullary catecholamine release during insulin-induced hypoglycemia (4). We showed that the increase in plasma Epi concentration during insulininduced hypoglycemia is unaltered by selective AT 1receptor blockade in both rats and humans (34,35).…”
mentioning
confidence: 70%
“…As an additional mechanism, ACE inhibitors may impair the release of epinephrine during hypoglycemia, which is considered one of the most important counterregulatory hormones during periods of severe depressions in blood glucose. In favor of this, hypoglycemia-induced elevations in epinephrine were inhibited by anti-angiotensin I (ANGI) antibodies [8], angiotensin II (ANGII) antagonism with saralasin [8,9], inhibition of ACE [8][9][10][11], and inhibition of AT 1 and AT 2 receptors [11,12] in most but not all [13] studies.…”
Section: Introductionmentioning
confidence: 99%
“…Accordingly, nephrectomy or treatment with a non-selective Ang II receptor antagonist nearly abrogates catecholamine release from cat adrenal medulla in response to the stress of insulin-induced hypoglycemia (Bumpus, et al 1980). Ang II also induces catecholamine biosynthesis by elevating gene expression of the catecholamine biosynthetic enzymes, tyrosine hydroxylase (TH) and phenylethanolamine N-methyltransferase (PNMT) (Stachowiak, et al 1990b).…”
Section: Introductionmentioning
confidence: 99%